THE ROLE OF SOCIAL MEDIA MARKETING, BRAND AWARENESS AND E-WOM TO INCREASE PURCHASE DECISION - Lena Ellitan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
Social capital plays an important role in the entrepreneurial process, research shows that social capital is strongly related to the creation of opportunities in several industries. Various platforms are used to build Brand Awareness online marketing tools are Social Media Marketing, and promotions carried out by customers by word of mouth (E-WOM), these two promotional techniques have an effect on improving a brand, thus making customers decide to make a purchase. Besides E-WOM, Brand Awareness is also the most important symbol in electronic word of mouth. In a sense, which states that if the existence of a brand is getting stronger, it will affect the subconscious of consumers, so that the wider the influence given to consumers frequently, the greater the influence for consumers to contemplate and discuss about the brand. Apart from that, there is an impact from the role of Social Media Marketing, which participates in upholding the brand to market the products sold. the use of social media provides an opportunity for companies to increase Brand Awareness of the brand, it is influenced by the use of social media which can increase the value of attractiveness, engage in communication between consumers, and increase consumer intimacy with the brand. This article aims to discuss the role of Social Media Marketing, Brand Awareness, and E-Wom in influencing consumer purchasing decisions.